2000
DOI: 10.1093/ndt/15.7.994
|View full text |Cite
|
Sign up to set email alerts
|

Increased blood levels of platelet‐activating factor in insulin‐dependent diabetic patients with microalbuminuria

Abstract: These results indicate an association between increased production of PAF and enhanced glomerular permeability in microalbuminuric IDD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 19 publications
2
23
0
3
Order By: Relevance
“…In regard to patients with DM 1, Cavallo-Perin et al 28 did not find any difference in PAF-AH activity among groups of patients with DM 1 without microalbuminuria, with microalbuminuria, and control subjects. Although they did not find any difference in PAF-AH activity among the groups…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…In regard to patients with DM 1, Cavallo-Perin et al 28 did not find any difference in PAF-AH activity among groups of patients with DM 1 without microalbuminuria, with microalbuminuria, and control subjects. Although they did not find any difference in PAF-AH activity among the groups…”
Section: Discussionmentioning
confidence: 89%
“…3). The stepwise multiple regression using PAF-AH activity as a dependent variable and age, gender, BMI, HbA1c, HDL and LDL as independent variables showed HDL and LDL as independent explanatory variables of changes in PAF-AH activity (step 1: r = 0.231, r2 studied, Cavallo-Perin et al 28 and Nathan et al 27 demonstrated that PAF levels are increased in patients with DM 1, and that this would be basically associated with a higher production of this particle. The disagreement between data found by these authors and our own may reflect the characteristics of the population studied -our sample had a lower age range, no microvascular complications and lower BMI, as well as the sample size -42 diabetics versus 7 patients with microalbuminuria and 7 without microalbuminuria assessed by Cavallo-Perin et al The higher PAF-AH activity in patients with DM 1 may represent an attempt at protection against pathophysiological mechanisms induced by increased levels of PAF found in these patients 34 or may exert pro-inflammatory and pro-atherogenic effects 30,32,33 .…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Plateletactivating factor (PAF) is an ether lipid of choline, and its presence has been demonstrated in a variety of eye tissues, including the retina, ciliary body, and iris (1,8,27). PAF and its metabolite lyso-PAF are potent inflammatory lipids, and PAF and lyso-PAF levels are elevated in serum of type 1 diabetic patients (4,10), as well as in oxygen-induced retinopathy (2). Intravenous injection of PAF into rabbits induced an intense ischemia accompanied by a marked plasma leakage (26).…”
mentioning
confidence: 99%
“…Some studies demonstrate that patients with DM have decreased activity of PAF-AH [9,36]. Cavallo-Perin et al [37] did not find any difference in PAF-AH activity between groups of patients with DM1 and control subjects. In our study, we did oxidative stress.…”
Section: Discussionmentioning
confidence: 93%